On the tracks of an uninvited guest, the Asian tiger mosquito, Aedes albopictus in Cyprus - Riccardo Piccinno; Giulia Fiorenza; Marlen Ines Vasquez; Jeremy Bouyer; Gregoris Notarides; Ludvik Marcus Gomulski; Soteris Meletiou; Mustafa Akiner; Antonios Michaelakis; Federico Forneris; Giovanni Maga; Giuliano Gasperi; et al. (Parasites & Vectors)
Abstract Background Aedes albopictus, the Asian tiger mosquito, which is listed among the world's 100 most dangerous invasive species, is the main vector of chikungunya, dengue and Zika viruses. This mosquito species has rapidly dispersed and invaded much of the globe assisted by its life history traits and high propagule pressure driven by human activities. Aedes albopictus is currently widespread across mainland Europe and the Mediterranean region, including the islands. Cyprus remained free of Ae. albopictus until October 2022, when specimens were recorded for the first time in Limassol district, including the port area. Understanding the processes associated with the introduction, expansion and establishment of this vector in Cyprus is of primary importance to mitigate its dispersal on the island, and to implement control methods to prevent disease outbreaks. A genetic analysis of these invasive specimens collected in Limassol district and in areas from the Central Mediterranean was performed to obtain a genetic portrait of the demographic history of the invasive mosquitoes on Cyprus. Methods We applied highly polymorphic simple sequence repeat (SSR) markers to the Ae. albopictus mosquitoes collected in Cyprus and to specimens from Italy, France, Switzerland, the Balkans, Greece and Turkey to construct an SSR individual genotype dataset that would enable the invasion pattern of Ae. albopictus in Cyprus to be traced. Bayesian clustering analyses using STRUCTURE and BayesAss version 3 were employed to derive information on the degree of ancestry among Cypriot and Mediterranean mosquitoes and on recent mosquito movements both within Cyprus and between Cyprus and the Central Mediterranean areas. Results The Cypriot mosquitoes appear to be highly polymorphic with no signs of genetic drift due to recent founder effects. An ongoing mosquito dispersal within the Limassol district was detected, suggesting the presence of established, hidden adventive populations. These mosquitoes share a high degree of ancestry with those in the Balkans and parts of northern Italy that border the Adriatic Sea. Conclusions Considering the trade connections of Limassol port, Cyprus with the Balkans and the Adriatic Italian region, we hypothesise that these areas may be involved in the incursion of Ae. albopictus into Cyprus. As the Balkan and Italian mosquitoes display high competence for CHIKV, questions arise about possible arbovirus outbreaks in Cyprus and highlight the need to implement surveillance and control measures. Graphical Abstract